Removal of toxic mercury from petroleum oil by newly synthesized molecularly-imprinted polymer - Khairi, Nor Ain Shahera; Yusof, Nor Azah; Abdullah, Abdul Halim; Faruq, Mohammad (MDPI AG, 2015)
In recent years, molecularly-imprinted polymers (MIPs) have attracted the attention of several researchers due to their capability for molecular recognition, easiness of preparation, stability and cost-effective production. By taking advantage of these facts, Hg(II) imprinted and non-imprinted copolymers were prepared by polymerizing mercury nitrate stock solution (or without it) with methacrylic acid (MAA), 2-hydroxyl ethyl methacrylate (HEMA), methanol and ethylene glycol dimethacrylate (EGDMA) as the monomer, co-monomer solvent (porogen) and cross-linker, respectively. Thus, the formed Hg(II) imprinted polymer was characterized by using Fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (FESEM), Brunauer, Emmett and Teller (BET) and thermal gravimetric analysis (TGA). The separation and preconcentration characteristics of Hg(II) imprinted polymer were investigated by solid phase extraction (SPE) procedures, and an optimal pH of 7 was investigated as ideal. The specific surface area of the Hg(II) imprinted polymer was found to be 19.45 m2/g with a size range from 100 to 140 µm in diameter. The maximum adsorption capacity was observed to be 1.11 mg/g of Hg(II) imprinted beads with 87.54% removal of Hg(II) ions within the first 5 min. The results of the study therefore confirm that the Hg(II) imprinted polymer can be used multiple times without significantly losing its adsorption capacity.